Respuesta :
Answer:
[tex] {(1 - 2x)}^{p} = 1 + ( - 2x)p + \frac{1}{2!} p(p - 1) {( - 2x)}^{2} + ... \\ \frac{4}{2!} p(p - 1) = 40 \\ p(p - 1) = 20 \\ {p}^{2} - p = 20 \\ {p}^{2} - p - 20 = 0\\ ( p - 5)(p + 4) = 0\\ p = 5 \: or \: p = - 4 \\ \because \: p > 0 \\ \therefore \: p = 5[/tex] Apply the binomial expansion...
The value of P for the given binomial expansion when calculated is; p = 5
How to Solve Binomial Expansions?
We are told that when we expand the expression (1 - 2x)^p, that the coefficient of x² is 40.
The general formula for binomial expansion is;
(x + y)ⁿ = ⁿC₀ xⁿ y⁰ + ⁿC₁ xⁿ⁻¹ y₁ + ⁿC² xⁿ⁻² y₂ + ... + ⁿCₙ x⁰ yⁿ
Applying that general formula to our question, we have;
(-2x + 1)^p = 1 + (-2x)p + [p(p - 1)/2!](-2x)² + ......
Thus, simplifying this gives;
[p(p - 1)/2!](-2x)² = -2p(p - 1)x²
Since the coefficient of x² is 40, then we have;
-2p(p - 1) = 40
p² - p = -20
p² - p + 20 = 0
Using online quadratic equation calculator, we have;
p = 5
Read more about Binomial Expansions at; https://brainly.com/question/13602562
#SPJ2